(untitled) (University Heart Journal, 2008)
A nine years old patient was referred to our cardiac surgery department with the complaints of recurrent respiratory tract infection since early childhood with growth retardation. Initial treatment was given by different level of doctors but his condition was not improving permanently. His guardian denied any family history of such disease. An examination revealed normal vital sings with a systolic murmur in the left parasternal region in the second intercostal space. Roentgenogram of the chest showed both the central pulmonary arteries are enlarged with right ventricular type of cardiomegaly. Two-dimensional echocardiography with colour Doppler study showed a large A-P window (Size- 19.3 mm) with bidirectional shunt with severe pulmonary hypertension (PASP = 93 mm of Hg) and normal aortic and pulmonary valve. The patient underwent surgical treatment (Transaortic Sauvage patch closure) after an optimum preoperative treatment. Post operatively he behaved well. All the parameters were within normal limit. He was asymptomatic at the time of discharge. Â Â Â University Heart Journal Vol.4(1) January 2008 Â